Diamond crystallization from an Mg–C system under high pressure, high temperature conditions. Issue 26 (14th July 2015) - Palyanov, Y. N.; Borzdov, Y. M.; Kupriyanov, I. N.; Khokhryakov, A. F.; Nechaev, D. V.
<x xml:space="preserve">Abstract</x> The effects of temperature and kinetics on diamond crystallization in the Mg–C system under high pressure, high temperature conditions are established.